Autophagy regulates the Wnt/GSK3β/β-catenin/cyclin D1 pathway in mesenchymal stem cells (MSCs) exposed to titanium dioxide nanoparticles (TiO2NPs). (2020) - Yu, Shunbang; Wang, Feng; Bi, Yujie; Wang, Pu; Zhang, Rui; Bohatko-Naismith, Joanna; Zhang, Xudong; Wang, He
Graphical abstract: Abstract: The application of titanium dioxide nanoparticles (TiO2 NPs) is on the increase, and so the number of studies dedicated to describing this material's biological effects. Previous studies have presented results indicating the controversial impact of TiO2 NPs on cell fate regarding death and survival. We speculate that this may be due to focusing on each of the subject cells as an isolated individual. In this study, we made a difference by looking at the subject cells as an interrelated population. Specifically, we exposed mesenchymal stem cells (MSCs) to TiO2 NPs and observed cell death and stimulation of proliferation among the cell population. Our data shows that the exposure to TiO2 NPs initiated autophagy, which led to an increase in extracellular Wnt protein levels and increased Wnt/GSK3β/β-catenin/cyclin D1 signalling in the cell population. Autophagy inhibitor repressed the effects of TiO2 NPs, which indicates that β-catenin regulation was dependent on TiO2 NPs-induced autophagy. The inhibition of β-catenin resulted in dysregulation of cyclin D1 protein expression level. In conclusion, following exposure to TiO2 NPs, MSCs undergo autophagy, which induces cell proliferation among the cell population by upregulation of cyclin D1 through the Wnt/GSK3β/β-catenin pathway.